Legal basis of foreign models of organizing the activities of prosecution bodies - Cherpak , Serhii (Actual problems of law (Aktual’ni problemi pravoznavstva), 2025)
The article provides a comprehensive analysis of the organization and functioning of prosecution offices in different legal systems, including the continental (Romano-Germanic), Anglo-Saxon, and socialist models. Each system’s features, advantages, and limitations are scrutinized, focusing on core principles such as independence, accountability, and functional autonomy. The study delves into the hierarchical and centralized structure of the continental model, with specific examples from France and Germany, where the role of prosecutors is defined by legal traditions and regulatory frameworks. The Anglo-Saxon model, exemplified by the United States and the United Kingdom, is explored for its decentralized nature, prosecutorial autonomy, and the distinctive practice of electing some prosecutors, which enhances public accountability but raises concerns about potential politicization. The socialist model, as observed in China and post-Soviet states, is characterized by a broader supervisory mandate and centralized control, which, while effective in certain contexts, often undermines prosecutorial independence due to close ties with executive power. Particular attention is paid to the challenges and opportunities associated with integrating international standards into prosecutorial systems. The study highlights key instruments such as the United Nations Guidelines on the Role of Prosecutors and the European Charter on the Status of Prosecutors, emphasizing their role in ensuring transparency, professionalism, and protection from undue political influence. The article also discusses Ukraine’s efforts to reform its prosecution system, addressing the legacy of excessive centralization inherited from the Soviet model and the need for greater functional independence and accountability. The research identifies several priority directions for reforming prosecution in Ukraine, including adopting best practices from both continental and Anglo-Saxon models. Recommendations include improving transparency in prosecutorial activities, decentralizing decision-making processes, and introducing mechanisms for public oversight to bolster trust in the institution. By aligning national reforms with international standards, the article argues that Ukraine can build a prosecution system capable of upholding the rule of law, defending public interests, and ensuring justice in a democratic society. This analysis contributes to the broader discourse on the adaptation of prosecutorial systems in transitioning democracies, providing a roadmap for balancing centralized control and independence to meet modern governance challenges.